Pemetaan Aktor dan Jaringan Hubungan Antar Aktor dalam Pembangunan Pedesaan - Yunindyawati; Tri Agus Susanto; Eva Lidya; Lili Erlina; Maulana (Jurnal Penyuluhan, 2022)
This research is to examine the actors mapping and the networking of actors relation in the wetland rural development process, the case study at Ulak Kembahang 1 district of Pemulutan Barat Ogan Ilir Regency province of South Sumatera. The purpose of this research is to analyzes the positive implications and consequences of the rule and position of each actor in the rural development process. Mix method is used in this study, combine the quantitative and qualitative method. The results shows that the rural development process not only determine by village government but also determine by many actors in the rural society for example the public figures, the religious leaders, the young man organization (Karang Taruna), the women’s organization (PKK), the women’s religious organization, the business women of songket craft, and the man and women’s activities. These actors are grouped in the three types, namely the individual actors, the organizational actors, and the combined of individual and organizational actors. Based on gender, the actors involved consisted of the women (44%) and the man (56%). Networking of the relations actors based on power/interest shows a positive relationship. The degree of power and interest of the each actor are varies from low, middle, and high, measured by lower score (11) to highest score (19).